Comparison of Inlet Geometry in Microfluidic Cell Affinity Chromatography - Li, Peng (2011)
Cell separation based on microfluidic affinity chromatography is a widely used methodology in cell analysis research when rapid separations with high purity are needed. Several successful examples have been reported with high separation efficiency and purity; however, cell capture at the inlet area and inlet design has not been extensively described or studied. The most common inlets—used to connect the microfluidic chip to pumps, tubing, etc—are vertical (top-loading) inlets and parallel (in-line) inlets. In this work, we investigated the cell capture behavior near the affinity chip inlet area and compared the different performance of vertical inlet devices and parallel inlet devices. Vertical inlet devices showed significant cell capture capability near the inlet area, which led to the formation of cell blockages as the separation progressed. Cell density near the inlet area was much higher than the remaining channel, while for parallel inlet chips cell density at the inlet area was similar to the rest of the channel. In this paper, we discuss the effects of inlet type on chip fabrication, nonspecific binding, cell capture efficiency, and separation purity. We also discuss the possibility of using vertical inlets in negative selection separations. Our findings show that inlet design is critical and must be considered when fabricating cell affinity microfluidic devices.